Case Report: Improving Verbal Retrieval Deficits With High Definition Transcranial Direct Current Stimulation Targeting the Pre-Supplementary Motor Area in a Patient With Chronic Traumatic Brain Injury - Chiang, Hsueh-Sheng; Shakal, Scott; Vanneste, Sven; Kraut, Michael; Hart, John (Frontiers in Neurology, 2021)
We report a patient who has cognitive sequalae including verbal retrieval deficits after severe traumatic brain injury (TBI). The cortico-caudate-thalamic circuit involving the pre-Supplementary Motor Area (pre-SMA) has been proposed to underlie verbal retrieval functions. We hypothesized that High Definition-transcranial Direct Current Stimulation (HD-tDCS) targeting the pre-SMA would selectively modulate this circuit to remediate verbal retrieval deficits. After the patient underwent 10 sessions of 20 minutes of 1 mA HD-tDCS targeting the pre-SMA, we documented significant improvements for verbal fluency and naming, and for working memory and executive function tasks that involve the frontal lobes. The effects persisted for up to 14 weeks after completion of HD-tDCS treatment. We also demonstrated normalization of the event-related potentials suggesting modulation of the underlying neural circuit. Our study implicates that region-specific non-invasive brain stimulation, such as HD-tDCS, serves as a potential individualized therapeutic tool to treat cognitive deficits by inducing longer-lasting neuroplasticity even in the chronic phase of TBI.